In vivo measurement of the effective atomic number of breast skin using spectral mammography. (30th October 2018) - Berggren, Karl; Eriksson, Mikael; Hall, Per; Wallis, Matthew G; Fredenberg, Erik
Abstract: X-ray characteristics of body tissues are of crucial importance for developing and optimizing x-ray imaging techniques, in particular for dosimetry and spectral imaging applications. For breast imaging, the most important tissues are fibro-glandular, adipose and skin tissue. Some work has and is being done to better characterize these tissue types, in particular fibro-glandular and adipose tissue. In the case of breast skin, several recent studies have been published on the average skin thickness, but with regards to x-ray attenuation, the only published data, to the knowledge of the authors, is the elemental composition analysis of Hammerstein et al (1979 Radiology 130 485–91). This work presents an overview of breast skin thickness studies and a measurement of the effective atomic number ( ) of breast skin using spectral mammography., which together with the density forms the attenuation, is used to validate the work by Hammerstein et al, and the dependence of clinical parameters on is explored. Measurements were conducted on the skin edge of spectral mammograms using clinical data from a screening population ( n   =  709). The weighted average of breast skin thickness reported in studies between 1997 and 2013 was found to be mm. Mean was found to be 7.365 (95% CI: 7.364, 7.366) for normal breast skin and 7.441 (95% CI: 7.440, 7.442) for the nipple and areola. of normal breast skin is in agreement with Hammerstein et al, despite the different methods and larger sample size used. A small but significant increase in was found with age, but the increase is too small to be relevant for most applications. We conclude that normal breast skin is well described by a 1.56 mm skin layer and the elemental composition presented by Hammerstein et al (1979 Radiology 130 485–91) and recommend using these characteristics when modelling breast skin.